Screening for Fusarium Antagonistic Bacteria From Contrasting Niches Designated the Endophyte Bacillus halotolerans as Plant Warden Against Fusarium - Slama, Houda Ben; Cherif-Silini, Hafsa; Chenari Bouket, Ali; Qader, Mallique; Silini, Allaoua; Yahiaoui, Bilal; Alenezi, Faizah N.; Luptakova, Lenka; Triki, Mohamed Ali; Vallat, Armelle; Oszako, Tomasz; Rateb, Mostafa E.; et al. (Frontiers in Microbiology, 2019)
Date palm (Phoenix dactylifera L.) plantations in North Africa are nowadays threatened with the spread of the Bayoud disease caused by Fusarium oxysporum f. sp. albedinis, already responsible for destroying date production in other infected areas, mainly in Morocco. Biological control holds great promise for sustainable and environmental-friendly management of the disease. In this study, the additional benefits to agricultural ecosystems of using plant growth promoting rhizobacteria (PGPR) or endophytes are addressed. First, PGPR or endophytes can offer an interesting bio-fertilization, meaning that it can add another layer to the sustainability of the approach. Additionally, screening of contrasting niches can yield bacterial actors that could represent wardens against whole genera or groups of plant pathogenic agents thriving in semi-arid to arid ecosystems. Using this strategy, we recovered four bacterial isolates, designated BFOA1, BFOA2, BFOA3 and BFOA4, that proved very active against F. oxysporum f. sp. albedinis. BFOA1–BFOA4 proved also active against 16 Fusarium isolates belonging to four species: F. oxysporum (with strains phytopathogenic of Olea europaea and tomato), F. solani (with different strains attacking O. europaea and potato), F. acuminatum (pathogenic on O. europaea) and F. chlamydosporum (phytopathogenic of O. europaea). BFOA1–BFOA4 bacterial isolates exhibited strong activities against another four major phytopathogens: Botrytis cinerea, Alternaria alternata, Phytophthora infestans, and Rhizoctonia bataticola. Isolates BFOA1–BFOA4 had the ability to grow at temperatures up to 35°C, pH range of 5–10, and tolerate high concentrations of NaCl and up to 30% PEG. The isolates also showed relevant direct and indirect PGP features, including growth on nitrogen-free medium, phosphate solubilization and auxin biosynthesis, as well as resistance to metal and xenobiotic stress. Phylogenomic analysis of BFOA1–BFOA4 isolates indicated that they all belong to Bacillus halotolerans, which could therefore considered as a warden against Fusarium infection in plants. Comparative genomics allowed us to functionally describe the open pan genome of B. halotolerans and LC-HRMS and GCMS analyses, enabling the description of diverse secondary metabolites including pulegone, 2-undecanone, and germacrene D, with important antimicrobial and insecticidal properties. In conclusion, B. halotolerans could be used as an efficient bio-fertilizer and bio-control agent in semi-arid and arid ecosystems.